Tobacco curly shoot virus Down-Regulated the Expression of nbe-miR167b-3p to Facilitate Its Infection in Nicotiana benthamiana - Wu, Rui; Wu, Gentu; Wang, Lyuxin; Wang, Xu; Liu, Zhuoying; Li, Mingjun; Tan, Wanzhong; Qing, Ling (Frontiers in Microbiology, 2021)
Tobacco curly shoot virus (TbCSV) belongs to the genus Begomovirus of the family Geminiviridae, and causes leaf curling and curly shoot symptoms in tobacco and tomato crops. MicroRNAs (miRNAs) are pivotal modulators of plant development and host-virus interactions. However, the relationship between TbCSV infection and miRNAs accumulation has not been well investigated. The present study was conducted to analyse different expressions of miRNAs in Nicotiana benthamiana in response to the infection of TbCSV via small RNAs sequencing. The results showed that 15 up-regulated miRNAs and 12 down-regulated miRNAs were differentially expressed in TbCSV infected N. benthamiana, and nbe-miR167b-3p was down-regulated. To decipher the relationship between nbe-miR167b-3p expression and the accumulations of TbCSV DNA, pCVA mediation of miRNA overexpression and PVX based short tandem target mimic (STTM) were used in this study. It was found that overexpression of nbe-miR167b-3p attenuated leaf curling symptom of TbCSV and decreased viral DNA accumulation, but suppression of nbe-miR167b-3p expression enhanced the symptoms and accumulation of TbCSV. PRCP, the target gene of nbe-miR167b-3p, was silenced in plants using VIGS and this weakened the viral symptoms and DNA accumulation of TbCSV in the plants. Overall, this study clarified the effect of nbe-miR167b-3p on plant defence during TbCSV infection, and provided a framework to reveal the molecular mechanisms of miRNAs between plants and viruses.